2016
DOI: 10.5812/hepatmon.40774
|View full text |Cite
|
Sign up to set email alerts
|

Liver Mitochondrial DNA Copy Number and Deletion Levels May Contribute to Nonalcoholic Fatty Liver Disease Susceptibility

Abstract: BackgroundThere is growing evidence that deficiencies observed in the mitochondrial DNA (mtDNA) functions could play an important role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). We hypothesized that genetic variations in mtDNA could affect the mitochondrial function and contribute to the NAFLD susceptibility.ObjectivesIn this study, the possible association of the mtDNA copy number and 4,977-bp deletion levels with NAFLD susceptibility in a sample of Iranian population was evaluated.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
(46 reference statements)
6
19
2
Order By: Relevance
“…Our findings of increased mitochondrial DNA copy numbers in the NAFLD patients and its positive correlations with oxidants (TBARS) may represent a compensatory response to a heightened oxidative injury. Similar to our results, Kamfar S et al found increased mtDNA copy number associated with NAFLD when comparing 43 Iranian obese NAFLD patients (BMI~44) with 20 obese control subjects (BMI~34) [ 22 ]. However, their report showed a much higher increase in mtDNA copy number (3.7-fold, compared to obese control) than our study (58%, compared to non-NAFLD HD patients).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings of increased mitochondrial DNA copy numbers in the NAFLD patients and its positive correlations with oxidants (TBARS) may represent a compensatory response to a heightened oxidative injury. Similar to our results, Kamfar S et al found increased mtDNA copy number associated with NAFLD when comparing 43 Iranian obese NAFLD patients (BMI~44) with 20 obese control subjects (BMI~34) [ 22 ]. However, their report showed a much higher increase in mtDNA copy number (3.7-fold, compared to obese control) than our study (58%, compared to non-NAFLD HD patients).…”
Section: Discussionsupporting
confidence: 90%
“…Mitochondria perform key cellular functions in fat and energy homeostasis through free fatty acid oxidation, electron transfer, and production of ATP and reactive oxygen species [ 21 ]. Disruption of fatty acid oxidation and excessive oxidative stress may be associated with mitochondrial dysfunction, leading to lipid accumulation [ 22 ]. Moreover, mitochondria and their DNA are the main targets of free radicals and are susceptible to oxidative damage [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…MtDNA copy number is a measure of mitochondrial function and reflects oxidant-induced cell damage 13 . The relative mtDNA copy number is approximately 3.7-fold higher in patients with non-alcoholic fatty liver disease than in healthy subjects 14 . Defective mtDNA replication can accelerate aging and reduce the lifespan of mice 15 .…”
mentioning
confidence: 93%
“…Nevertheless, studies on the association of NAFLD with liver mtDNAcn were contradictory. For instance, increased liver mtDNAcn has been reported in mice and patients with NAFLD (15,16), whereas another study indicated that liver mtDNAcn was decreased in patients with NAFLD (17). A previous study has indicated that the mtDNAcn of leukocytes is well-related to that in the rat liver (18), but the studies on the association between leukocyte mtDNAcn and NAFLD are Abbreviations: mtDNAcn, mitochondrial DNA copy number; NAFLD, nonalcoholic fatty liver disease; TNF-α, tumor necrosis factor α; IL-6, interleukin 6; GR, glutathione reductase; SOD, superoxide dismutase; 8-oxo-dG, 8-oxo-2 ′deoxyguanosine; NASH, non-alcoholic steatohepatitis; WC, waist circumference; AGT, abnormal glucose tolerance; NGT, normal glucose tolerance; HbA 1c , hemoglobin A 1c ; HOMA-IR, Homeostatic Model Assessment of Insulin Resistance; ALT, alanine transaminase; AST, aspartate transaminase; UA, uric acid; HDL-C, high-density lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; TC, cholesterol; TG, triglyceride.…”
Section: Introductionmentioning
confidence: 99%